2014
DOI: 10.1007/s00167-014-3364-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectations of primary and revision anterior cruciate ligament reconstruction

Abstract: Prospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(182 citation statements)
references
References 40 publications
6
171
4
1
Order By: Relevance
“…Rehabilitation is frequently focused on specific joint and functional parameters (6-9), often not considering psychological issues. On the other hand, physical and mental issues are strictly connected and complementary in the human being (10)(11)(12)(13). The improvement of psychological status influences the somatic status.…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation is frequently focused on specific joint and functional parameters (6-9), often not considering psychological issues. On the other hand, physical and mental issues are strictly connected and complementary in the human being (10)(11)(12)(13). The improvement of psychological status influences the somatic status.…”
Section: Introductionmentioning
confidence: 99%
“…The high rates of chondral lesions observed at the time of revision ACLR may be associated with the high rates of osteoarthritis development following revision ACLR (Salmon, Pinczewski, Russell, & Refshauge, 2006). Despite an overall reduction in patient expectations for revision ACLR compared to the very high expectations reported prior to primary ACLR, 96% of patients expect no risk or a slightly increased risk of developing osteoarthritis (compared to a healthy knee) 10 years following revision ACLR, 88% percent expect to return to the same level of sport, and all patients expect to have a normal or nearly normal knee after revision surgery (Feucht et al, 2014). In contrast to these expectations, only one in every two patients return to pre-injury sport following revision ACLR (Grassi et al, 2015) and reported rates of knee osteoarthritis four to eight years after revision ACLR range from 37% to 80% (Kamath, 2011).…”
Section: Subsequent Injury and Revision Surgerymentioning
confidence: 99%
“…Factors associated with a reduced likelihood of returning to sport included older age at the time of ACLR, female sex, participating in non-elite sport, a high fear of re-injury, low psychological readiness to return to sport and negative emotional responses to ACLR (Ardern, Taylor, Feller, & Webster, 2012a;Ardern et al, 2014b). Despite the low rates of return to sport reported in the literature, as many as 91% of patients expect to return to pre-injury sport within one year of ACLR (Feucht et al, 2014). This mismatch between return to sport expectations and actual return to sport rates could negatively impact on QOL and postoperative satisfaction.…”
Section: Return To Pre-injury Sportmentioning
confidence: 99%
See 2 more Smart Citations